Police innovation contrasting perspectives - Weisburd, David 1954-; Braga, Anthony Allan 1969- (Cambridge studies in criminology, 2006)
Over the last three decades American policing has gone through a period of significant change and innovation. In what is a relatively short historical time frame the police began to reconsider their fundamental mission, the nature of the core strategies of policing, and the character of their relationships with the communities that they serve. This volume brings together leading police scholars to examine eight major innovations which emerged during this period: community policing, broken windows policing, problem oriented policing, pulling levers policing, third party policing, hot spots policing, Compstat and evidence-based policing. Including advocates and critics of each of the eight police innovations, this comprehensive book assesses the evidence on impacts of police innovation on crime and public safety, the extent of the implementation of these new approaches in police departments, and the dilemmas these approaches have created for police management. This book will appeal to students, scholars and researchers